A Igreja Universal do Reino de Deus e a reconfiguração do espaço público religioso brasileiro = The Universal Church of the Kingdom of God and the reconfiguration of the Brazilian religious public space - Oro, Ari Pedro (Ciencias sociales y religión, 2015)
This paper analyzes the protagonism by the Universal Church of the Kingdom of God in the sense of producing reconfigurations in the current Brazilian religious public space. This occurs in different dimensions but this text is atem especially in iurdiana production monumentalization the religious, through the building of so-called cathedrals of faith, deployed in strategic places of the cities. In doing so the Universal defies Catholic hegemony to establish itself as legitimate religion in the public sphere, while their mega constructions tend to provoke a mimetic effect on other religious backgrounds who compete with her in public space. As a result, we have the diversification and expansion of religion in public space, which is a perspective for understanding the Brazilian secularization.